Genetic Susceptibility to Retinopathy of Prematurity: A Paradigm for Preterm Disease Traits - Manzoor Ahmad Malik; Swati Shukla; Arpna Srivastava; Jasbir Kaur (Delhi Journal of Ophthalmology)
Retinopathy of prematurity (ROP) is a vasoproliferative retinal disorder in premature infants that can lead to blindness and the incidence is increasing with increased survival of infants born at very early gestational age and low birth weight. Majority of common diseases are complex and multifactorial resulting from the interplay of genetic components and environmental factors. As no single gene or genetic variant on its own can cause the disease pathology, complexities associated with common diseases present unique challenges for management and therapy. Genome wide association and resequencing projects together with gene environment interaction studies are expected to further define the causal relationships that connect genetic variants to ROP pathogenesis and should assist in better design of prevention and intervention. This review summarizes the recent literature on ROP with a special focus to recognize the genetic basis of the disease.